ERN eUROGEN guidelines on the management of anorectal malformations, part IV: organization of care and communication between providers - Aubert, Ophelia; Irvine, Willemijn; Aminoff, Dalia; Baauw, Ivo de; Cascio, Salvatore; Cretolle, Célia; Iacobelli, Barbara Daniela; Lacher, Martin; Mantzios, Konstantinos; Midrio, Paola; Miserez, Marc; Sarnacki, Sabine; et al. (European journal of pediatric surgery, 2025)
Introduction Being born with an anorectal malformation (ARM) can have profound and lifelong implications for patients and parents. Organization of care and communication between health care providers is an overlooked area of patient care. The European Reference Network eUROGEN for rare and complex urogenital conditions assembled a panel of experts to address these challenges and develop comprehensive guidelines for the management of ARM. Methods The Dutch Quality Standard for ARM served as the basis for the development of guidelines. Literature was searched in Medline, Embase, and Cochrane. The ADAPTE method was utilized to incorporate the newest available evidence. A panel of 15 experts from seven European countries assessed currency, acceptability, and applicability of recommendations. Recommendations from the Dutch Quality Standard were adapted, adopted, or rejected and recommendations were formed considering all available evidence, expert consensus, and the European context. Results Aspects pertaining to organization of care, patient/parent/health care provider communication, and referral and collaboration between providers caring for ARM patients were assessed. Two new studies were identified. In total, the panel adapted 12 recommendations, adopted 7, and developed 2 de novo. The overall level of newly found evidence was considered low and most recommendations were based on expert opinion.Conclusion Collaborative care and organization of care are gaining importance in the field of ARM. This guideline gives practical guidance on how to achieve better communication and collaboration between all involved parties, applicable at the European level.
Online veröffentlicht: 11. Oktober 2024
Gesehen am 01.04.2025